The maths game : using instructional games to teach mathematics - Booker, George (Wellington, N.Z. : NZCER, 2000)
The role of instructional games. Instructional games in the teaching. Instructional games in the teaching. Instructional games in the teaching. Using instructional games to foster. Using instructional games in a mathematics.
Keywords: Mathematics; Games in mathematics education; Mathematics -- Study and Teaching (Elementary); Games in mathematics education